A6.1 Antibody Response Against Porphyromonas Gingivalis and Matrix Metalloproteinase-3 are Associated with Anti-Citrullinated Protein Antibody in Rheumatoid Arthritis, but only Matrix Metalloproteinase-3 is a Predictive Factor of Response to Infliximab. (25th February 2013) - Rinaudo-Gaujous, M; Miossec, P; Blasco-Baque, V; Gaudin, P; Thomas, T; Moreau, A; Genin, C; Paul, S; Marotte, H
Abstract : Background and Objectives: This study evaluates clinical and biological markers of rheumatoid arthritis (RA) severity including matrix metalloproteinase (MMP-3) and Porphyromonas gingivalis (P. gingivalis) serology during infliximab treatment and highlights predictive factors of response to infliximab. Materials and Methods: Joint damage and severe periodontal disease were assessed in 101 RA patients included in this study. DAS28, anti-citrullinated protein antibodies (ACPA), anti- P. gingivalis antibody, and MMP-3 were monitored before and at 6 months of infliximab therapy. ACPA, anti- P. gingivalis antibody, and MMP-3 were determined by ELISA. Results: At baseline, ACPA titers were associated with anti- P. gingivalis LPS-specific antibodies titers (P < 0.05). Anti- P. gingivalis antibodies were not significantly correlated with clinical, biological, or destruction parameters of RA disease. At 6 months of infliximab therapy, MMP-3 level decreased (from 119 ± 103 ng/ml to 62.44 ± 52 ng/ml; P < 0.0001), whereas P. gingivalis antibody levels remained at the same level. DAS28 and inflammation markers (CRP and ESR) also decreased significantly during infliximab therapy (P < 0.05) as ACPA levels (P < 0.001). Only high MMP-3 level at baseline was associated with infliximab efficacy (P < 0.01). Conclusions: MMP-3 level can be a useful marker of the efficacy of infliximab in RA patients. The treatment did not affect anti- P. gingivalis antibodies.